2021
DOI: 10.1371/journal.pone.0247004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low high-density lipoprotein among young adults receiving antiretroviral therapy in Zambia: An opportunity to consider non-communicable diseases in resource-limited settings

Abstract: Background With the introduction of effective antiretroviral therapy (ART), people living with HIV (PLWH) are surviving longer and are at risk for developing metabolic abnormalities that contribute to cardiovascular disease (CVD). In Sub-Saharan Africa (SSA), there is a paucity of epidemiological data on lipid profiles among young adults receiving ART. This study aimed to estimate the prevalence of low high-density lipoprotein cholesterol (HDL-c), a cardioprotective lipid class, and whether it differed by age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
5
6
0
Order By: Relevance
“…These observations were further confirmed in a multivariate regression analysis, after adjusting for confounders. Our findings are comparable to prior studies that have analysed blood lipid disorders in adolescents and adults living with HIV living in similar settings ( Ombeni and Kamuhabwa, 2016 ; Fiseha et al., 2021 ; Hamooya et al., 2021 ; Tilahun et al., 2021 ). A recent Zambian cross-sectional study found a high prevalence (63%) of low HDL-c in ART experienced young adults living with HIV aged 18-24 years and that these young individuals were about three times more likely to have low HDL-c than older individuals ( Hamooya et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These observations were further confirmed in a multivariate regression analysis, after adjusting for confounders. Our findings are comparable to prior studies that have analysed blood lipid disorders in adolescents and adults living with HIV living in similar settings ( Ombeni and Kamuhabwa, 2016 ; Fiseha et al., 2021 ; Hamooya et al., 2021 ; Tilahun et al., 2021 ). A recent Zambian cross-sectional study found a high prevalence (63%) of low HDL-c in ART experienced young adults living with HIV aged 18-24 years and that these young individuals were about three times more likely to have low HDL-c than older individuals ( Hamooya et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are comparable to prior studies that have analysed blood lipid disorders in adolescents and adults living with HIV living in similar settings ( Ombeni and Kamuhabwa, 2016 ; Fiseha et al., 2021 ; Hamooya et al., 2021 ; Tilahun et al., 2021 ). A recent Zambian cross-sectional study found a high prevalence (63%) of low HDL-c in ART experienced young adults living with HIV aged 18-24 years and that these young individuals were about three times more likely to have low HDL-c than older individuals ( Hamooya et al., 2021 ). Also similar to our findings, the prevalence of low HDL-c and hypertriglyceridemia has also been observed in other studies with similar settings to be higher on ART experienced HIV+ than HIV- children ( Mandal et al., 2016 ; Dirajlal-Fargo et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Metabolic risks such as weight gain, dyslipidemia and hyperglycemia, which are part of the metabolic syndrome, have been identified in patients on cART which can alter normal endothelial function ( 72 , 134 , 135 , 154 , 155 ). Sax et al showed that weight gain was greater in more recent trials and with the use of newer integrase strand transfer inhibitor (INSTIs) such as dolutegravir than protease inhibitors ( 135 ).…”
Section: Epithelial Sodium Channel and Cardiovascular Diseasementioning
confidence: 99%
“…In addition, aldosterone stimulates both the innate and adaptive immune systems leading to macrophages and T cells accumulation in the kidneys, heart, and vasculature which contribute to the development of hypertension and other cardiometabolic diseases ( 165 ). The persistence of immune activation in HIV ( 144 , 166 ) and the metabolic toxicity associated with cART ( 72 , 134 , 135 , 154 , 155 ) may potentially play an additive or multiplicative role on the effects of aldosterone and ENaC activation, and therefore increase the risk of hypertension in PWH. Given the widespread use of dolutegravir, it is worth prospectively investigating the impact of weight gain on ENaC function in PWH.…”
Section: Epithelial Sodium Channel and Cardiovascular Diseasementioning
confidence: 99%